Case Report: A Severe Paediatric Presentation of COVID-19 in APDS2 Immunodeficiency - Sanchez Clemente, Nuria; Penner, Justin; Breuer, Judith; Ip, Winnie; Booth, Claire (Frontiers in Immunology, 2022)
Critical respiratory manifestations of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) are rare in children and little is known about how immunocompromised children respond to the infection. We report a case of a 4-year-old boy with activated PI3K delta syndrome type 2 (APDS2) with a protracted and severe COVID-19 course with both inflammatory and acute respiratory features. He was treated with remdesivir, nitazoxanide, high dose corticosteroids and tocilizumab and made a full recovery. We propose that remdesevir may be used in combination with nitazoxanide to improve viral clearance and reduce the chance of resistance in treating acute severe SARS-CoV-2 infection.